Preliminary Assessment On The Distribution Of Heavy Metal Within Chenaam Estuary Using Gis - Arumugam, Harshaan (Universiti Sains Malaysia, 2022)
Water pollution negatively impacts both human and aquatic organisms; hence, the evaluation and critical observation of water contamination and its effects have become crucial. Sungai Air Itam receives wastes from various sources such as agricultural activity, boating activity, aquaculture and municipal solid wastes. As a result, Sungai Air Itam’s water and sediment became polluted with heavy metals. A preliminary assessment was conducted on the concentration of heavy metals in water and sediment samples collected along the partially reconstructed irrigation channel of Sungai Air Itam in Kampung Sungai Chenaam. 11 sampling points were identified from the upstream up till the downstream near the river mouth of Sungai Air Itam. The final sampling point is located at the water gate of Sungai Air Itam Jetty. For each sample, the total concentration of 21 heavy metals was determined via the Inductively Coupled Plasm Optical-Emission Spectroscopy (ICP-OES) method. From the measurements, significant results were obtained on 8 types of heavy metals, namely chromium (Cr), iron (Fe), lead (Pb), cadmium (Cd), copper (Cu), manganese (Mn), nickel (Ni) and zinc (Zn). Cr was not detected in any of the water samples collected throughout Sungai Air Itam. Therefore, overall concentrations of Fe, Pb, Cd, Cu, Mn, Ni and Zn in water samples ranged from 0.51-2.49, 0.00-0.12, 0.0089-0.028, 0.057-0.063, 0.066-0.57, 0.00-0.11 and 0.046-0.068 mg/L respectively. On the other hand, overall concentrations of Cr, Fe, Pb, Cd, Cu, Mn, Ni and Zn in sediment samples ranged from 0.063-0.38, 28.53-191.04, 0.00-0.24, 0.032-0.12, 0.11-0.76, 0.32-2.79, 0.00-0.24 and 0.30-2.94 mg/L respectively. The decreasing trend of heavy metals were observed in surface water as Fe>Mn>Ni>Cu>Pb>Zn>Cd>Cr and in sediment as Fe>Mn>Zn>Cu>Cr>Pb>Ni>Cd.